Larvicidal efficacy of the crude leaf extracts of Eucalyptus camaldulensis Dehn (Myrtales: Myrtaceae) against the mosquito larvae of Culex quinquefasciatus Say (Diptera: Culicidae) - Khan, Humayun Reza; Sultana, Nigar; Sharmin, Prova (Dhaka University Journal of Biological Sciences, 2018)
Eucalyptus camaldulensis was assayed to evaluate the larvicidal efficacy of its leaf extracts against the 3rd instar larvae of Culex quinquefasciatus at five dose concentrations (viz. 0.25, 0.50, 0.75, 1.0, 1.25, 1.5, 2.0, 2.5 and 3.0) in five solvents (viz. chloroform, ethanol, di-chloromethane, acetone and water) based extracts after 24 hrs exposure. Among all the extracts the shade dried chloroform based leaf extracts showed the highest larvicidal efficacy (viz. 42.67, 56.67, 68.0, 92.67 and 100%) at low dose concentrations of 0.25, 0.50, 0.75, 1.0 and 1.25, respectively while the sun dried water based leaf extracts showed the lowest larvicidal efficacy (viz. 21.33, 30.67, 48.67, 58.0 and 74.0%) at high dose concentrations of 1.0, 1.5, 2.0, 2.5 and 3.0, respectively among the ten different experimental conditions. The relative potency of ten types of crude leaf extracts of E. camaldulensis against the mosquito larvae are shown as follows in decreasing order on the basis of LC50 value : Shade dried chloroform based leaf extract (0.356 mg/ml) > sun dried chloroform based leaf extract (0.400 mg/ml) > shade dried di-chloromethane based leaf extract (0.411 mg/ml) > sun dried dichloromethane based leaf extract (0.579 mg/ml) > shade dried ethanol based leaf extract (0.736 mg/ml) > sun dried ethanol based leaf extract (0.817 mg/ml) > shade dried acetone based leaf extract (1.000 mg/ml) > sun dried acetone based leaf extract (1.251 mg/ml) > shade dried water based leaf extract (1.807 mg/ml) > Sun dried water based leaf extract (2.020 mg/ml).The effectiveness of the shade dried leaf extracts was shown higher than the sun dried leaf extracts under comparable condition. No mortality was observed in control treatment. The study revealed that these leaf extracts have the potency to consider as an effective larvicidal agent. It is an alternative source for developing a novel larvicide for controlling the mosquito species. Dhaka Univ. J. Biol. Sci. 27(2): 135-144, 2018 (July)